2021
DOI: 10.1038/s42003-021-02794-8
|View full text |Cite
|
Sign up to set email alerts
|

Archaeogenetic analysis of Neolithic sheep from Anatolia suggests a complex demographic history since domestication

Abstract: Sheep were among the first domesticated animals, but their demographic history is little understood. Here we analyzed nuclear polymorphism and mitochondrial data (mtDNA) from ancient central and west Anatolian sheep dating from Epipaleolithic to late Neolithic, comparatively with modern-day breeds and central Asian Neolithic/Bronze Age sheep (OBI). Analyzing ancient nuclear data, we found that Anatolian Neolithic sheep (ANS) are genetically closest to present-day European breeds relative to Asian breeds, a con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
2
14
1
Order By: Relevance
“…The phylogeographic structure that we observed in modern mitochondrial sheep haplogroups, where haplogroup B predominates in western populations and haplogroup A does so in eastern populations, is consistent with various reports [e.g., (33,(41)(42)(43)]. Such structure has been explained by means of multiple domestication origins (33,(44)(45)(46)(47), the domestication of different wild populations or species (33), introgression (41), and lineage sorting-and-gene drift (33).…”
Section: Haplogroups As Potential Markers Of Independent Domesticationsupporting
confidence: 91%
See 1 more Smart Citation
“…The phylogeographic structure that we observed in modern mitochondrial sheep haplogroups, where haplogroup B predominates in western populations and haplogroup A does so in eastern populations, is consistent with various reports [e.g., (33,(41)(42)(43)]. Such structure has been explained by means of multiple domestication origins (33,(44)(45)(46)(47), the domestication of different wild populations or species (33), introgression (41), and lineage sorting-and-gene drift (33).…”
Section: Haplogroups As Potential Markers Of Independent Domesticationsupporting
confidence: 91%
“…In this regard, we show here that early Neolithic Aşıklı Höyük from Central Anatolia had haplogroups A, B, D, E, and unreported Z at high frequencies (0.161, 0.355, 0.306, 0.065, and 0.113, respectively) which is broadly consistent with what is reported in Neolithic sheep (see fig. S14) (41)(42)(43). These findings most definitely refute multiple domestication origins as an explanation for the modern distribution of these haplogroups.…”
Section: Haplogroups As Potential Markers Of Independent Domesticationmentioning
confidence: 73%
“…By comparing the allele frequency in long-tailed and short-tailed sheep in multiple breeds, we observed that the above-mentioned derived allele G occurs more frequently in long-tailed sheep breeds (Supplementary Table S5 ). Further, at this position, we observed only the ancestral allele in Urial, Argali, Snow sheep, Dall sheep, Canadensis and two ancient (~8000 years) sheep genomes 31 . On the other side out of 16 investigated Asiatic mouflon 3 were heterozygous C/G and 2 homozygous G/G for the point mutation.…”
Section: Resultsmentioning
confidence: 70%
“…By comparing the allele frequency in long-tailed and short-tailed sheep in multiple breeds, we observed that the above-mentioned derived allele G occurs more frequently in long-tailed sheep breeds (Supplementary Table S4). Further, at this position, we only observed the ancestral allele in Urial, Argali, Snow sheep, Dall sheep, Canadensis and two ancient (~8,000 years) sheep genomes 63 . On the other side out of 16 investigated Asiatic mouflon 3 were heterozygous C/G and 2 homozygous G/G for the point mutation.…”
Section: Resultsmentioning
confidence: 73%